Severe monkeypox with superimposed bacterial infection in an immunocompetent patient: A case report. (2022) - Manoharan, Aysswarya; Braz, Beatriz X.; McBride, Andrew; Hernandez, Salma; Balfour, Monica; Quiroz, Tanya; Powell, Alexis; Rodriguez, Allan; Morris, Stephen; Gonzales-Zamora, Jose A.
Abstract: Monkeypox, a member of the Orthopoxvirus genu, has been the center of global attention since it has been declared a public health emergency by the World Health Organization. Typically, it is a self-limiting disease; however, it can occasionally have severe presentations in patients with underlying conditions, such as HIV, malignancy, and transplantation. In this article, we will present a case of an immunocompetent patient with a severe presentation of monkeypox. The patient presented with facial pustules with superimposed bacterial infection; furthermore, he had painful vesicles in oral and nasal mucosa and the penis. Dermatologic conditions such as atopic dermatitis has been associated with severe monkeypox. While our patient does not have a history of atopic dermatitis, he does report contact dermatitis as well as a history of skin infections. Researchers have hypothesized that disruption of the skin barrier allows for proliferation of the monkeypox virus; therefore, it is important to take a thorough history of the patient's skin conditions. Lastly, we described the use of Tecovirimat in our patient. Although it is impossible to demonstrate the efficacy of this medication without a randomized clinical trial, our patient seemed to have a faster improvement of the lesions after initiating this antiviral.